Critical Land Mapping of Protected Forest Areas in Sukamakmur District, Bogor Regency - Ramadhan, Aditya (Journal of Geographical Sciences and Education, 2024)
Sukamakmur District is one of the areas in Bogor Regency where disasters often occur related to critical land conditions. This situation is often associated with changes in land cover as population growth continues. This research aims to identify and map critical land using a geographic information system (GIS) in Sukamakmur District. The method used is tumpeng stacking analysis with classification, scoring and weighting. There are 4 classes of critical land in Sukamakmur District, the largest percentage of low potentially critical land is 14,008 ha (82.32%). Then followed by slightly critical land with an area of 2,777.5 ha (16.32%), critical land with an area of 215.5 ha (1.27%), and very critical land with an area of only 16 ha (0.09%) of total area. This indicates that critical land for protected forests in Sukamakmur District is still relatively low.